Small Bowel Transit and Altered Gut Microbiota in Patients With Liver Cirrhosis - Liu, Yang; Jin, Ye; Li, Jun; Zhao, Lei; Li, Zhengtian; Xu, Jun; Zhao, Fuya; Feng, Jing; Chen, Huinan; Fang, Chengyuan; Shilpakar, Rojina; Wei, Yunwei (Frontiers in Physiology, 2018)
Disturbance of the gut microbiota is common in liver cirrhosis (LC) patients, the underlying mechanisms of which are yet to be unfolded. This study aims to explore the relationship between small bowel transit (SBT) and gut microbiota in LC patients. Cross-sectional design was applied with 36 LC patients and 20 healthy controls. The gut microbiota was characterized by 16S rRNA gene sequencing. The Firmicutes/Bacteroidetes (F/B) ratio and the Microbial Dysbiosis index (MDI) were used to evaluate the severity of microbiota dysbiosis. The scintigraphy method was performed in patients to describe the objective values of SBT. Patients were then subdivided according to the Child-Pugh score (threshold=5) or SBT value (threshold=0.6) for microbiota analysis. LC patients were characterized by an altered gut microbiota; F/B ratios and MDI were higher than healthy controls in both Child_5 (14.00±14.69 vs. 2.86±0.99, p<0.01; 0.49±0.80 vs. -0.47±0.69, p<0.01) and Child_5+ (15.81±15.11 vs. 2.86±0.99, p< 0.01; 1.11±1.05 vs. -0.47±0.69, p<0.01) sub-groups in patients. Difference in the gut microbiota between Child_ 5 and Child_5+ patients was inappreciable, but the SBT was relatively slower in Child_5+ patients (43±26% vs. 80±15%, p<0.05). Compared with the Child-Pugh score indicators, SBT showed stronger associations with bacterial genera. A clear difference in the gut microbiota was observed between SBT_0.6- and SBT_0.6+ patients (Pr(>F)=0.0068, pMANOVA), with higher F/B ratios and MDI in SBT_0.6- patients (19.71±16.62 vs. 7.33±6.65, p<0.01; 1.02±0.97 vs. 0.20±0.58, p<0.01). Similar results were observed between the SBT_0.6- and SBT_0.6+ sub-groups of patients with normal liver function and a Child-Pugh score of 5. SBT was negatively correlated with both the F/B ratio and MDI (r=-0.34, p<0.05; r=-0.38, p<0.05). Interestingly, an increased capacity for the inferred pathway “bacterial invasion of epithelial cells” in patients, was highly negatively correlated with SBT (r=-0.57, p<0.01). The severity of microbiota dysbiosis in LC patients depends on SBT rather than Child-Pugh score. SBT per se might be significantly related to the gut microbiota abnormalities observed in patients with LC.